Evaluation of the effects of cryogenic freezing on fruits - Lizeth N. Santiago Castillo (2025)
Cryogenic freezing is considered one of the most efficient techniques for fruit preservation, as it extends shelf life while preserving sensory and nutritional characteristics. Its effectiveness lies in the formation of small, uniform ice crystals that maintain cell structure, reducing physical damage and limiting microbial and enzymatic activity. Success depends on factors such as freezing rate, fruit type, storage time, and thawing process. In mangoes, rapid freezing methods like Individual Quick Freezing (IQF) have shown to better preserve texture, color, and antioxidants compared to conventional techniques. In blueberries, liquid nitrogen application maintains high levels of vitamin C and firmness, although it can cause surface cracking if the process is not carefully controlled. In kiwis, the effects vary according to soluble solids content and fruit region, influencing cold tolerance and structural damage. In durian, cryogenics has proven more effective than traditional freezing, preserving both internal and external quality for a longer period. Emerging technologies such as ultrasound, high pressure, magnetic fields, and the use of cryoprotectants, especially polysaccharide nanoparticles, enhance this technique by reducing recrystallization and optimizing fruit stability during freezing and thawing, making cryogenics a strategic tool for the modern food industry.